# Creating a loop with for loop

5 ビュー (過去 30 日間)
Miguel Anliker 2019 年 11 月 7 日
Commented: Rena Berman 2019 年 12 月 12 日
How do you loop A11-A33 correctly?
function [determinant , inverse ] = invanddet3by3(A)
A11 = invanddet2by2sol(A([2,3], [2,3])); % Cofactors 3x3 matrix A
A12 = -invanddet2by2sol(A([2,3], [1,3]));
A13 = invanddet2by2sol(A([2,3], [1,2]));
A21 = -invanddet2by2sol(A([1,3], [2,3]));
A22 = invanddet2by2sol(A([1,3], [1,3]));
A23 = -invanddet2by2sol(A([1,3], [1,2]));
A31 = invanddet2by2sol(A([1,2], [2,3]));
A32 = -invanddet2by2sol(A([1,2], [1,3]));
A33 = invanddet2by2sol(A([1,2], [1,2]));
D = [A11 A12 A13; A21 A22 A23; A31 A32 A33]; % Adju Matrix
determinant = A(1,1) * A11 + A(1,2) * A12 + A(1,3) * A13; % Deter of A
if determinant == 0
inverse=[];
else
inverse = D' / determinant; % Inv of A
end
end

#### 4 件のコメント

Miguel Anliker 2019 年 11 月 7 日
I have to create a loop so that code lines 2-10 are simplified
Stephen Cobeldick 2019 年 11 月 7 日
"I have to create a loop so that code lines 2-10 are simplified"
Then don't use numbered variables.
Using numbered variables is a sign that you are doing something wrong.
Rena Berman 2019 年 12 月 12 日

サインイン to comment.

### 採用された回答

JESUS DAVID ARIZA ROYETH 2019 年 11 月 7 日
solution:
function [determinant , inverse ] = invanddet3by3(A)
D=zeros(3);
s=[2 3; 1 3; 1 2];
for k=1:size(D,1)
for j=1:size(D,2)
D(k,j)=(-2*mod(k+j,2)+1)*invanddet2by2sol(A(s(k,:),s(j,:)));
end
end
determinant=sum(A(1,:).*D(1,:));
if determinant == 0
inverse=[];
else
inverse = D' / determinant; % Inv of A
end
end

#### 3 件のコメント

Miguel Anliker 2019 年 11 月 7 日
Just a small question :
Can you explain a bit more in detail how you got the loop function "for" and if possible simplify it ?
Thank you Jesus!
JESUS DAVID ARIZA ROYETH 2019 年 11 月 7 日
yes, it is even possible to eliminate the for cycle, and receive any dimension input, basically if the sum of the row and the column gives odd then it is multiplied by -1 otherwise multiplied by 1 ((-2 * mod (k + j, 2) +1 ) -> 2x-1 --> if x==1 then y=1 else if x==0 then y=-1), I also noticed that the number 1 corresponds [2,3], the number 2 corresponds [1,3] and so on
Rik 2019 年 11 月 7 日
Comment posted as answer by Miguel Anliker:
Thank you for the explanation.

サインイン to comment.